MULTI AKAD (AL-UQUD AL-MURAKKABAH) DI PERBANKAN SYARIAH PERSPEKTIF FIQH MUAMALAH - Aryanti, Yosi (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
Multiple Agreement (al-Uqud al-Murakkabah) is one of contemporary agreements in Islamic banking whose implementation develops in line with business developments Multiple Agreement basically is an agreement whic is made by two parties in carrying out transactions that cover two elements or more of agreement, such as trading and ijarah. Agreements in sharia transactions are modified from the existing agreements in which such agreements are found in almost all sharia products. The development of the uses of agreement need strong analysis concerning the validity of the agreements, especially those whic have been modified. This study therefore aims at presenting perspectives of Islamic schlars (ulama) and their analysis toward the concepts of Multiple Agreement.